2020
DOI: 10.1177/0092055x20922896
|View full text |Cite
|
Sign up to set email alerts
|

Embodying Inequality: Using Ethnographic Data to Teach Intersectionality

Abstract: This article analyzes the effectiveness of an activity we developed to help students better understand intersectionality. Intersectionality is an analytic concept that signifies ways that inequalities may overlap to create unique forms of privilege and subjugation. In the activity, students use assigned vignettes from the perspective of research participants in our own ethnographic data (including excerpts from interviews and field notes) to interact with peers assigned both similar and dissimilar perspectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Our results mirror those of Brinkman and Donohue (2020), who emphasized that in teaching intersectionality one should pay specific attention to promoting students' skills related to the selfreflection of their own positions and backgrounds (also Crawford 2012; Davis and Gentlewarrior 2015). For example, Gardner and McKinzie (2020) used vignettes to provide concrete 'real-life' examples of the material consequences of intersectionality as they impact people in their everyday lives. In our data, 10 of 14 students wrote in their feedback that they felt face-to-face teaching and shared reflections would have been beneficial, and these would have potentially supported a deeper discussion of the issues.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our results mirror those of Brinkman and Donohue (2020), who emphasized that in teaching intersectionality one should pay specific attention to promoting students' skills related to the selfreflection of their own positions and backgrounds (also Crawford 2012; Davis and Gentlewarrior 2015). For example, Gardner and McKinzie (2020) used vignettes to provide concrete 'real-life' examples of the material consequences of intersectionality as they impact people in their everyday lives. In our data, 10 of 14 students wrote in their feedback that they felt face-to-face teaching and shared reflections would have been beneficial, and these would have potentially supported a deeper discussion of the issues.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, Gardner and McKinzie's (2020) study among undergraduate sociology students found that students grasped intersectionality as a useful tool for understanding how people experience overlapping forms of inequality and privilege. They employed vignettes to provide concrete 'real-life' examples of the material consequences of intersectionality on people's everyday lives.…”
Section: Teaching Intersectionalitymentioning
confidence: 99%
“…Sociologists have extensively documented effective strategies for inclusive teaching practices—particularly by enhancing cultural competency and empathy (Hart and Kocher 2023), employing trauma-informed strategies (Bedera 2021), and illuminating structural bias and prejudices against marginalized communities (Nowakowski et al 2016). A growing concern with inclusive teaching practices in sociology classrooms is the need to address the multiple power systems that reproduce inequality and privilege (Smith-Tran 2020), such as understanding how intersectionality can be used as a teaching-learning tool for conceptualizing interlocking systems of oppression and privilege in classrooms (Crenshaw 1989; Gardner and McKinzie 2020). To inclusively teach a Sociology of Sex and Gender course, for example, educators must address racism, classism, heterosexism, and other forms of discrimination in their curriculum when discussing sex and gender inequalities in society (Nowakowski et al 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While some exercises are contained within the classroom, many pedagogical approaches to teaching ethnography involve assignments that require students to venture into field sites and collect data in person, either in teams of students (Schmid 1992; Trujillo 1999), individually (Halfpenny 1981; Hamilton and Gilbert 2005), or at minimum, in classroom exercises with other students (Hsiung 2008). Others have advanced techniques for using feature-length films to teach ethnographic methods (Leblanc 1998) or textual data from their own ethnographic projects to teach specific concepts (Gardner and McKinzie 2020), which do not require the same forms of direct social context; still, many researchers argue that hands-on experience is needed to truly master these skills (e.g., Bernard 2018; Madden 2017; O’Reilly 2009; Woods 2005).…”
Section: Literature Reviewmentioning
confidence: 99%